Identification of T-cell epitopes in the Hepatitis C virus genotype 4 proteome: a step towards epitope-driven vaccine development - Abdel-Hady, Karim Mohamed Ali (AUC Knowledge Fountain, 2014)
Hepatitis C is an inflammatory infectious disease of the liver caused by the Hepatitis C Virus (HCV). It is a global pandemic, chronically inflicting 150 million people worldwide, with millions of new infections arising annually. The standard therapy of HCV is expensive, associated with severe side effects, and has variable success rates. Thus far, no HCV vaccine has been developed, owing to the challenges that faced and still face its development. Despite these challenges, several attempts have been taken to develop a vaccine, some of which have progressed to phase II clinical trials. Most of these attempts, however, have focused on HCV genotypes 1 and 2 as vaccine targets, and almost no attention has been given to HCV genotype 4 (HCV-4), the viral genotype most prevalent in the Middle East and Central Africa. In an attempt to fill this gap in HCV-4 vaccine research, this project describes the in silico identification of a group of highly conserved and immunogenic T-cell epitopes from the HCV-4 proteome, using the iVAX immunoinformatics toolkit (EpiVax Inc., RI, USA), as a first step towards the development of an epitope-driven vaccine against the viral genotype. Furthermore, it puts forth a fast and inexpensive method for the validation of the results retrospectively using the repository of empirical HCV immune epitope data on the Immune Epitope Database (IEDB). 90 HLA class I and 14 HLA class II epitopes were identified. From those, 20 HLA class I epitopes were found to be previously uncharacterized, while the in silico HLA binding predictions for 27 others (class I and class II) have been retrospectively validated. The retrospective validation results for 4 of the identified HLA class II epitopes were confirmed by a pilot HLA class II binding assay. Furthermore, an investigation of the conservancy of a selected set of the identified epitopes in newly re-sequenced HCV strains from the Egyptian population was performed. The identified and retrospectively validated set of epitopes constitutes a good target for further immunogenicity testing and epitope-driven vaccine development against HCV-4.